2021
DOI: 10.7150/jca.44649
|View full text |Cite
|
Sign up to set email alerts
|

U three protein 14a (UTP14A) promotes tumour proliferation and metastasis via the PERK/eIF2a/GRP78 signalling pathway in oesophageal squamous cell carcinoma

Abstract: Metastasis and malignant proliferation are major obstacles to the treatment of oesophageal squamous cell carcinoma (ESCC), and UTP14A is associated with poor prognosis in ESCC. However, its mechanisms have not been fully elucidated. The TCGA and GEO databases were used to identify candidate target genes and possible downstream targets. Then, the effects were determined in vitro and in vivo through knockdown and overexpression techniques, and the mechanism was explo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…UTP14A (U three protein 14A) plays a key role in the synthesis of ribosomes and 18S rRNA; however, in the last few years, data have appeared on the association of this gene with some types of tumors—hepatocellular carcinoma, colorectal carcinoma, and esophageal squamous cell carcinoma [ 74 ]. The exact mechanisms of its activity are unknown, but we have shown for the first time that the expression of this gene correlates with genes involved in the development of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…UTP14A (U three protein 14A) plays a key role in the synthesis of ribosomes and 18S rRNA; however, in the last few years, data have appeared on the association of this gene with some types of tumors—hepatocellular carcinoma, colorectal carcinoma, and esophageal squamous cell carcinoma [ 74 ]. The exact mechanisms of its activity are unknown, but we have shown for the first time that the expression of this gene correlates with genes involved in the development of HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…Schatz et al [66] found that it signifcantly overexpressed EIF2S1, EIF5A, and EIF6 when compared to healthy tissue samples. Recently, Li et al [67] linked the UTP14A overexpression in oesophageal squamous cell carcinoma (ESCC) cells to the upregulation of PERK/eIF2a signaling pathway, leading to the cell cycle process and migration of ESCC cells. Te overexpression of OTSCC, oral tongue squamous cell carcinoma; BSCC, buccal squamous cell carcinoma; GO, Gene Ontology.…”
Section: Discussionmentioning
confidence: 99%
“…It has been noted that UTP14A is involved in the development of colorectal cancer by promoting angiogenesis, while the inhibition of UTP14A can improve the prognosis of patients [ 30 , 31 ]. The upregulation of UTP14A was associated with the progression of esophageal cancer [ 32 ]. Similarly, PIN2/TRF1-interacting telomerase inhibitor 1 (PinX1) is involved in the development of cancer through angiogenesis [ 33 ].…”
Section: Discussionmentioning
confidence: 99%